STAKEHOLDER ENGAGEMENT TO ENHANCE INTERVENTIONS FOR FAMILY CAREGIVERS OF PEOPLE WITH DEMENTIA. (11th November 2018) - McCarron, H; Finlay, J; Sims, T; Nikzad-Terhune, K; Gaugler, J
Abstract: Family members are prominent in providing necessary care to persons with dementia in the United States. Although there exist a number of evidence-based supports/interventions for family caregivers of persons with dementia, there is an increased call on the part of policymakers and researchers (e.g., the National Alzheimer's Project Act) to develop more stakeholder-centric interventions to result in services that have increased acceptability, utility, and translational potential. Prior research has identified community advisory boards (CABs) as a successful strategy to engage stakeholders in research and intervention development. Yet, little is known about the use of CABs when developing and refining interventions in dementia care. This article presents a case study of a CAB intended to strengthen the usability and feasibility of an online dementia caregiver resource: Care to Plan. Seven CAB meetings lasting 60–90 minutes each, took place over three years. Qualitative thematic analysis of meeting transcripts identified two major categories. First, the CAB process: who participated, how meetings were conducted, and issues that arose. Second, Care to Plan tool improvement: how CAB members provided key stakeholder perspectives that were vital to improving the tool as it related to the language, functionality, substance, and dissemination of the tool. The findings emphasize how CABs can play an important role in facilitating the development, utilization, and potential sustainability of meaningful, evidence-based interventions for dementia caregivers.